Rats with chronic spinal cord transection as a possible model for the at-level pain of paraplegic patients - Scheifer, Caroline; Hoheisel, Ulrich; Trudrung, Peter; Unger, Thomas; Mense, Siegfried (Neuroscience letters, 2002)
Patients with complete spinal cord injury (SCI) often suffer from chronic pain which is perceived around the segment of the lesion. The present study tests the hypothesis that chronic SCI pain is due to pathophysiological neuronal activity in the spinal segment just rostral to the SCI. In an animal model with complete chronic SCI, the impulse activity of single dorsal horn neurones was recorded in the segment rostral to the lesion. Following SCI, the neurones exhibited a higher background activity. Some neurones showed an abnormal type of activity which was not present under control conditions. The results support the hypothesis that increased and altered background activity just rostral to the lesion contributes to chronic at-level pain of paraplegic patients.
Gesehen am 01.09.2017